Arterial hypertension prevalence in patients with Type I diabetes mellitus (part 1) - E. Kh. Akhmetzyanova; D. U. Allaberdina (Российский кардиологический журнал)
Arterial hypertension (AH) prevalence inpatients with Type I diabetes mellitus (DM) aged after 18 years (by 1999 WHO criterions) in Bashkortostan Republic was studied. Dates of DM State Registry (DMSR) Bashkortostan's Republic were used. AH prevalence in Type I DM is composed among women 52%, among men - 37%. In Type I DM, was observed association women's sex with AH increase.